3X3 basketball at Tokyo 2020 Olympics: competition organization model - Zarubina, M. S.; Andryushchenko, L. B.; Averyasova, Yu. O.; Gineviciene, V.; Organ, I. V. (Theory and Practice of Physical Culture, 2020)
Objective of the study was to analyze the most effective competitive progress models for ratings and qualifications in the modern 3?3 basketball. Methods and structure of the study: During the study the following methods were applied: analysis, synthesis of video recordings of the basketball games and static protocols in 3x3 Basketball World Championships of 2018 and 2019 (96 games), European Championships of 2017, 2018, and 2020 (96 games), Russian Championships of 2018, 2019, and 2020 (249 games), World Tour stages of 2017, 2018 and 2019 (589 games); simulation method. Results and conclusions: The study of the models of organization of 3x3 basketball competitions at the international and national levels enabled to elaborate recommendations on the development of a national effective model of competitive activity: it is advisable to differentiate the work of the federations into two areas: professional and mass. To ensure high rating points and competitive experience at the international level club teams are to participate in 80% of competitions organized by FIBA (3x3 World Tour and 3x3 World Tour Qualifiers) and in other competitions - participation for the Russian national team and in national tournaments of the Russian Basketball Federation, intensify the work on the system for organizing and holding international competitions of the World Tour and World Tour Qualifiers. To attract new players in 3x3 basketball it is advisable to hold national competitions on the basis of the classical basketball model: Russian championships for different age groups, regional and municipal competitions; use reserve opportunities: organize prestigious tournaments during the off-season of classical basketball (May-September). The findings emphasize the importance of advanced trainings of physical education and sports specialists in the field of information technology, digital services and technologies. The article presents the analysis of the modern system for organizing and holding 3x3 basketball competitions. We identified the peculiarities of participation of national teams in competitions of different levels and elaborated recommendations on optimization of 3x3 basketball development aimed to raise the federation`s world ranking.